Convergent synthesis of diptoindonesin G. Issue 3 (17th January 2019) - Singh, Dileep Kumar; Kim, Ikyon
Graphical abstract: Highlights: A convergent and scalable synthetic approach to diptoindonesin G is described. Suzuki-Miyaura coupling and intramolecular Friedel-Crafts acylation as key steps. This route should be useful for synthesis of diptoindonesin G and its derivatives. Abstract: A convergent and scalable synthetic route to a tetracyclic oligostilbenoid natural product, diptoindonesin G, is described where Suzuki-Miyaura cross-coupling and intramolecular Friedel-Crafts acylation were employed to construct the central C ring of diptoindonesin G. Two fragments for cross-coupling reaction were readily synthesized with similar efficiency.